2004
DOI: 10.1038/sj.bjc.6602158
|View full text |Cite
|
Sign up to set email alerts
|

Mammography screening in the Netherlands: delay in the diagnosis of breast cancer after breast cancer screening

Abstract: In a prospective study we determined the frequency and causes of delay in the diagnosis of breast cancer after suspicious screening mammography. We included all women aged 50 -75 years who underwent biennial screening mammography in the southern breast cancer screening region of the Netherlands between 1 January 1996 and 1 January 2002. Clinical data, breast imaging reports, biopsy results and breast surgery reports were collected of all women with a positive screening result with a minimum of 2-year follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 22 publications
0
38
0
5
Order By: Relevance
“…van Dijck et al (1993) showed that a considerable percentage of interval cancers in a biennial screening programme appear de novo between two screening rounds. We related screening outcome parameters to the total breast cancer incidence after 2 years of follow-up rather than after 1 year of follow-up, as this will provide full information about the interval cancer rate and the total costs of follow-up in a biennial screening programme (Duijm et al, 2004b(Duijm et al, , 2008. Review of late interval cancers is part of the quality assurance and evaluation of the Dutch breast cancer screening programme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…van Dijck et al (1993) showed that a considerable percentage of interval cancers in a biennial screening programme appear de novo between two screening rounds. We related screening outcome parameters to the total breast cancer incidence after 2 years of follow-up rather than after 1 year of follow-up, as this will provide full information about the interval cancer rate and the total costs of follow-up in a biennial screening programme (Duijm et al, 2004b(Duijm et al, , 2008. Review of late interval cancers is part of the quality assurance and evaluation of the Dutch breast cancer screening programme.…”
Section: Discussionmentioning
confidence: 99%
“…For all women with a screening mammogram that was considered positive by at least one of the radiologists or radiographers, we collected data on diagnostic procedures undertaken, breast cancer diagnosis, histopathology, and TNM (tumour -node -metastases) classification (UICC, 1987) to identify screen-detected cancers. Procedures for the detection of interval cancers (interval cancers are breast cancers that are diagnosed in women after a negative screening examination) have been described previously (Duijm et al, 2004b). To determine whether an interval cancer could potentially have been a screen-detected cancer if all positive radiographer readings had been referred, we investigated if the mammographic abnormalities on the diagnostic films corresponded to any abnormalities registered by the radiographers at screening.…”
Section: Screening Follow-upmentioning
confidence: 99%
“…7,9 There may also be diagnostic delays, e.g., due to erroneous mammographic interpretations. 21 In the current study, any follow-up screening or early recall was discouraged but, if existing, not necessarily captured. This may affect comparability of the Finnish interval cancer rates with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Positive matches are manually checked to determine whether they involve an IC or a late diagnosis of a screen-detected (SD) cancer due to a delay during the diagnostic assessment. 22 The Dutch programme evaluation takes the loss to follow-up into account for women who died or moved away from their region before their next screening examination, and also the exact date of the next screening examination. 10 IC rates are then expressed as the number of IC divided by the number of women-years of follow-up within the corresponding time period.…”
Section: Methodsmentioning
confidence: 99%